Human mesenchymal stem cell transplantation changes proinflammatory gene expression through a nuclear factor‐κB‐dependent pathway in a rat focal cerebral ischemic model. Issue 11 (30th August 2013) - Wang, Hui; Nagai, Atsushi; Sheikh, Abdullah Md.; Liang, Xue Yun; Yano, Shozo; Mitaki, Shingo; Ishibashi, Yutaka; Kobayashi, Shotai; Kim, Seung U.; Yamaguchi, Shuhei
<x xml:space="preserve">Abstract</x> Previous studies have demonstrated the immunomodulatory functions of mesenchymal stem cells (MSCs) in cerebral ischemic rats. However, the underlying mechanisms are unclear. The purpose of this study is to investigate the effects of MSC transplantation on transcriptional regulations of proinflammatory genes in cerebral ischemia. Transient ischemia was induced by middle cerebral artery occlusion (MCAO) in adult male Sprague‐Dawley rats. After 24 hr, vehicle (PBS) or a human MSC line (B10) was transplanted intravenously. The neurological deficits, infarct volume, cellular accumulations, and gene expression changes were monitored by means of behavior tests, MRI, immunohistochemistry, Western blotting, laser capture microdissection, and real‐time PCR. In the core area of the B10 transplantation group, the number of ED1‐positive macrophage/microglia was decreased compared with the PBS group. In the core, nuclear factor‐κB (NF‐κB) was decreased, although CCAAT/enhancer‐binding protein β was not changed; both were expressed mainly in ED1‐positive macrophage/microglia. Likewise, mRNAs of NF‐κB‐dependent genes including interleukin‐1β, MCP‐1, and inducible nitric oxide synthase were decreased in ED1‐positive and Iba‐1‐positive macrophage/microglia in the B10 transplantation group. Moreover, upstream receptors of the NF‐κB pathway, including CD40 and Toll‐like receptor 2 (TLR2), were decreased. Immunofluorescence results showed that, in the B10 transplantation group, the percentages of NF‐κB‐positive, CD40‐positive, and TLR2‐positive cells were decreased in ED1‐positive macrophage/microglia. Furthermore, NF‐κB‐positive cells in the CD40‐ or TLR2‐expressing cell population were decreased in the B10 transplantation group. This study demonstrates that B10 transplantation inhibits NF‐κB activation, possibly through inhibition of CD40 and TLR2, which might be responsible for the inhibition of proinflammatory gene expression in macrophage/microglia in the infarct lesion. © 2013 Wiley Periodicals, Inc.